A SINGLE-BLIND, PLACEBO-CONTROLLED CLINICAL TRIAL OF LOCAL APPLICATION OF KOHL-CHIKNI DAWA-A UNANI COMPOUND FORMULATION IN THE PATIENTS OF PRE-MATURE SENILE CATARACT - ZEHRA ZAIDI; ABDUL NASIR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present clinical trial was undertaken to evaluate the safety, preventive/ curative efficacy of the local application of KCD in patients of premature senile cataract, to provide an economic, safe, and effective alternative treatment for it. Methods: The present prospective single-blind, placebo-controlled trial was undertaken at Majeedia Hospital, Hamdard University, New Delhi. The diagnosed patients of premature senile cataract were randomly allocated to three groups for local application of KCD/ placebo. Results: Ninety two patients completed the study period of 6 months. After treatment the results show that KCD was effective in the general amelioration of the signs, and symptoms of the premature senile cataract. KCD have some significant effect on grade I of PS Cataract as out of 52 cases; lens score was nil in 5 patients (9.6 %) but no effect on grades II and III premature senile cataract. Vision remains stationary in 44% cases during study period. Conclusion: The dose of KCD in two sticks BID was safe, and tolerable with no side effects. KCD was also effective in loss of vision in grade I of PSC. KCD have potential to modulate the progress of early premature senile cataract. A multicentric trial of the test drug on a larger sample size for a longer duration of five years as per WHO recommendation is required to establish the efficacy of the formulation on premature senile cataract.